On capacity evaluation for multi-state weighted k-out-of-n system. Issue 7 (9th August 2019) - Zhuang, Xinchen; Yu, Tianxiang; Shen, Linjie
ABSTRACT: Weighted k -out-of- n system has been widely used in various engineering areas. Performance of such system is characterized by the total capacity of the components. Therefore, capacity evaluation is of great importance for research on the behavior of the system over time. Capacity evaluation for binary weighted k -out-of- n system has been reported in the literature. In this paper, to shorten computational time, we first develop a multiplication method for capacity evaluation of binary weighted k -out-of- n system. We then generalize capacity evaluation to multi-state weighted k -out-of- n system. Recursive algorithm and multiplication algorithm are developed for capacity evaluation for such system. Comparison is made of the two methods in different aspects. An illustrative example of an oil transmission system is presented to demonstrate the implementation of the proposed methods.